ANALYSIS OF SYSTEM QUALITY, INFORMATION QUALITY AND PERCEIVED USEFULNESS TO USER SATISFACTION - Tiana Tiana; Bambang Sugiharto; Indah Umiyati (JASS (Journal of Accounting for Sustainable Society), 2019)
This study aims to test and analyze the quality of the system against perceived usefulness, the quality of information against perceived usefulness, the quality of the system to user satisfaction, Information Quality to user satisfaction and perceived usefulness to user satisfaction. The population in this research is employees teller and customer service department of Bank BJB in subang city. Sampling technique is nonprobability sampling by using purposive sampling method. The type of data used is primary data with questionnaire data collection method. Hypothesis testing used is Structural Equation Modeling (SEM) approach with variance Structural equation test or better known as Partial Least Square (PLS). The result of the research shows that Quality System has a significant positive effect on Perceived Usefulness, Quality of Information has a significant positive effect on Perceived Usefulness, Quality of System has a significant positive effect on user satisfaction, Information Quality has positive significant effect on user satisfaction, and Perceived Usefulness has no effect to User Satisfaction